Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1128/mcb.21.10.3351-3363.2001
|View full text |Cite
|
Sign up to set email alerts
|

A Single Point Mutation in the V3 Region Affects Protein Kinase Cα Targeting and Accumulation at Cell-Cell Contacts

Abstract: Given the importance of intercellular adhesion for many regulatory processes, we have investigated the control of protein kinase C␣ (PKC␣) targeting to the cell-cell contacts. We have previously shown that, upon treatment of the pituitary cell line GH3B6 with thyrotropin-releasing hormone (TRH) or phorbol 12-myristate 13-acetate (PMA), human PKC␣ (hPKC␣) is selectively targeted to the cell-cell contacts (42). Here we show that the D294G mutation of hPKC␣, previously identified in a subpopulation of human tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 49 publications
(59 reference statements)
2
36
0
2
Order By: Relevance
“…3B and C): 118 s for PKC␤1, 20 s for PKC␣, 15 to 20 min for PKCε, and 33 s for PKC␦ (see the videos in the supplemental material). Strikingly, the time during which PKC␤1 remained activated was identical to that of the D294G PKC␣ mutant (51). The fact that PKC␣ mutant activation is phase locked with [Ca 2ϩ ] i variations (51) suggests that the PKC␣ mutant has indeed switched from a Ca 2ϩ -independent to a Ca 2ϩ -dependent translocation as hypothesized above.…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations
“…3B and C): 118 s for PKC␤1, 20 s for PKC␣, 15 to 20 min for PKCε, and 33 s for PKC␦ (see the videos in the supplemental material). Strikingly, the time during which PKC␤1 remained activated was identical to that of the D294G PKC␣ mutant (51). The fact that PKC␣ mutant activation is phase locked with [Ca 2ϩ ] i variations (51) suggests that the PKC␣ mutant has indeed switched from a Ca 2ϩ -independent to a Ca 2ϩ -dependent translocation as hypothesized above.…”
Section: Resultsmentioning
confidence: 53%
“…Strikingly, the time during which PKC␤1 remained activated was identical to that of the D294G PKC␣ mutant (51). The fact that PKC␣ mutant activation is phase locked with [Ca 2ϩ ] i variations (51) suggests that the PKC␣ mutant has indeed switched from a Ca 2ϩ -independent to a Ca 2ϩ -dependent translocation as hypothesized above. Conversely, the D187/246/248N PKC␤1 mutant, which accumu- The selective accumulation of PKC␣ and -at cell-cell contacts is dependent on PKC activity.…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…Moreover, it was reported that calponin, a cytoskeletal protein, may serve to regulate PKC by facilitating its phosphorylation (24). A recent study revealed that a functional and integral actin microfilament network is essential for translocation of PKC␣ from the cytosol to the plasma membrane (47).…”
Section: Discussionmentioning
confidence: 99%